2015
DOI: 10.9734/bjmmr/2015/19217
|View full text |Cite
|
Sign up to set email alerts
|

Early-Onset Severe Preeclampsia in Nigerian Women: Determining a Balance between Maternal Wellbeing and Fetal Survival in a Resource-Limited Setting

Abstract: Background: Preeclampsia in Nigerian women is considered to have a rapidly progressive clinical course. Aim: In the present study we sought to determine the most appropriate gestational age (GA) for delivery in severe preeclampsia occurring preterm to achieve optimal neonatal outcome, without causing undue maternal compromise. Study Design: A retrospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Enaruna et al observed that Severe anemia was 7.7-fold more associated with maternal mortality in severe preeclampsia cases than no anemia. 4 Abruption was seen in 8.88% cases than 0.5% controls, ARF was seen in 2.2% cases than in 0.5% control. Pulmonary edema seen in 5% cases, PPH occurred in 2.8% cases, CCF in 3.3%, HELLP in 1.6%, CVA 1.1%, Pulmonary embolism and DIC in 0.5% cases.…”
Section: Thus Incidence Of Preeclampsia In Sultania Zananamentioning
confidence: 84%
See 2 more Smart Citations
“…Enaruna et al observed that Severe anemia was 7.7-fold more associated with maternal mortality in severe preeclampsia cases than no anemia. 4 Abruption was seen in 8.88% cases than 0.5% controls, ARF was seen in 2.2% cases than in 0.5% control. Pulmonary edema seen in 5% cases, PPH occurred in 2.8% cases, CCF in 3.3%, HELLP in 1.6%, CVA 1.1%, Pulmonary embolism and DIC in 0.5% cases.…”
Section: Thus Incidence Of Preeclampsia In Sultania Zananamentioning
confidence: 84%
“…1 Enaruna et al found 30 years (range: 19 to 41) and Assis et al found that age above 30 years was associated with a risk for preeclampsia. 4,5 Andhra Pradesh found the highest prevalence of anaemia (68.4%) in the age group 20-24 years . There has been increased risk of anaemia among pregnant adolescents (teenage pregnancy) due to depleted iron stores that occurred during the adolescent growth spurt.…”
Section: Thus Incidence Of Preeclampsia In Sultania Zananamentioning
confidence: 99%
See 1 more Smart Citation